Grup Facebook Jual Beli Handphone sebagai Arena Pembentukan Modal Sosial: Analisis Critical Hacking dalam Perspektif Pierre Bourdieu - Andre Dwi Septian (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The rapid development of digital technology has transformed social media into a platform for economic interaction and the formation of social relationships. One example is Facebook Buy and Sell Handphone Groups, which serve not only as transaction platforms but also as digital arenas for the formation of social capital. This study aims to analyze the formation of social capital within Facebook Buy and Sell Handphone Groups using the Critical Hacking Analysis (CHA) approach from the perspective of Pierre Bourdieu. This research employed a qualitative method with a Critical Hacking Analysis approach. Data were collected through digital observation, in-depth interviews, and documentation involving group administrators, sellers, buyers, and active group members. Data were analyzed using the three levels of Critical Hacking Analysis, namely discourse analysis, practice analysis, and structural analysis, complemented by Platform Resistance Analysis (PRA) and Algorithmic Power Mapping (APM). The findings indicate that Facebook Groups function as digital arenas where social capital is formed through trust, community norms, and social networks that support economic activities. Facebook's algorithm also influences information visibility and transaction opportunities, encouraging members to develop adaptive strategies such as building digital reputations, utilizing testimonials, and increasing user engagement. These findings demonstrate that the formation of social capital results from the interaction between habitus, various forms of capital, the digital arena, and the platform's algorithmic mechanisms that shape power relations within social media-based online trading communities.